Distinct element method simulation of an analogue for a highly interlocked, non-persistently jointed rockmass - Bahrani, N; Kaiser, P.K; Valley, Benoît (My University, 2014)
A grain-based distinct element model is used to reproduce the laboratory response of both intact and granulated Wombeyan marble. The term “granulated” refers to a heat treated marble where the cohesion of grain boundaries has been destroyed. The unconfined compressive strength granulated marble is less than 50% of that of intact marble, while the strength of the granulated marble increases to about 80% of that of the intact marble at higher confining stresses. An iterative calibration approach is developed to match the unconfined and confined strengths of the models to those of intact and granulated marble. The simulation test results of the models of intact and granulated marble including the transition in the failure mode, stress-strain response, and the evolution of inter- and intra-grain micro-cracks with increasing confinement are discussed. The observed rapid strengthening effect, in terms of increasing confinement, is interpreted to be due to the high degree of grain assembly geometric interlock, which arises from the tight fit geometric shape of the grains as well as the roughness of the grain boundaries. It is suggested that the granulated marble can be considered to be an analogue for a highly interlocked, non-persistently jointed rockmass. It is shown that when the generalized Hoek–Brown failure criterion and the Geological Strength Index (GSI) are used to match the strength of the granulated marble at zero confinement, the confined strength of the granulated marble is underestimated by as much as a factor of two. Therefore, the confined strength of a highly interlocked, non-persistently jointed rockmass, with strong, brittle rock blocks, could be significantly higher than that predicted by commonly adopted empirical approaches. This has practical implications for the design of highly confined pillars and abutments, which is discussed in this paper.
Keywords: Grain-based model; Calibration; Non-persistently jointed rockmass; Interlocking; Confinement